2021
DOI: 10.1590/1519-6984.232661
|View full text |Cite
|
Sign up to set email alerts
|

First report the role of benthic macroinvertebrates as preys for native fish in Toltén river (38° S, Araucania region Chile)

Abstract: The Toltén river is located in the 137 years old Araucania region, Chile (38° S), and is characterized by low alterations through human interference due agriculture and towns in its surrounding basin, the presence of native fishes and salmonids, and by its lake effluent regime originated from Villarrica lake. The aim of the present study was to make a review of ecological role of the benthic inland water macroinvertebrates as preys for native fishes of the River Toltén, in order to understand their importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
2
3
0
Order By: Relevance
“…The most numerous species in these sectors were Meridialaris chiloense, Nousia delicata, Pelurgoperla personata and Ceratoperla schwabei, consistent with their environmental requirements for cold, highly oxygenated, turbulent water (Miserendino et al, 2018). These restricted distributions of Ephemeroptera and Plecoptera have been described for Argentinean and Chilean Patagonian river systems (Arenas, 1995;Oyanedel et al, 2008;Moya et al, 2009;Figueroa et al, 2007;Miserendino et al, 2018;De los Ríos-Escalante et al, 2020;Barile et al, 2021).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The most numerous species in these sectors were Meridialaris chiloense, Nousia delicata, Pelurgoperla personata and Ceratoperla schwabei, consistent with their environmental requirements for cold, highly oxygenated, turbulent water (Miserendino et al, 2018). These restricted distributions of Ephemeroptera and Plecoptera have been described for Argentinean and Chilean Patagonian river systems (Arenas, 1995;Oyanedel et al, 2008;Moya et al, 2009;Figueroa et al, 2007;Miserendino et al, 2018;De los Ríos-Escalante et al, 2020;Barile et al, 2021).…”
Section: Discussionsupporting
confidence: 63%
“…Few studies have been carried out in the rivers of Patagonian Chile (Figueroa et al, 2003, Moya et al, 2009Fierro et al, 2015;De los Ríos-Escalante et al, 2020;Barile et al, 2021), with some benthic studies based on stomach contents studies (Vargas et al, 2010;Barile et al, 2021); moreover, these descriptions are based on taxonomic categories rather than species-level identification. The Bíobío river is the only reference fluvial system in Chile for which the benthic and fish communities have been described (Arenas 1995).…”
Section: Sampling Proceduresmentioning
confidence: 99%
“…(2021), who found associations between groups reported and environmental parameters for Chilean North Patagonian rivers. In this scenario, the macroinvertebrate assemblage fauna in the studied river is similar to observations for central and southern Chilean rivers (35-40º S;Fierro et al, 2015;Figueroa et al, 2003Figueroa et al, , 2007Figueroa et al, , 2013Vega et al, 2020;Barile et al, 2021), where it was found marked differences in community structure in function to river zone, where it is possible found that in high zones there are shredders (Ephemeroptera, Plecoptera) that requires water quality with high oxygen content and low dissolved organic matter contents and nutrient concentration (Moya et al, 2009;Oyanedel et al, 2008;Miserendino et al, 2018;De los Ríos-Escalante et al, 2020;Solis-Lufi et al, 2021).…”
Section: Tablesupporting
confidence: 87%
“…wastewater discharges from a range of industrial activities. In some sections of the river system present an interruption of the natural flow, with the presence of agricultural and forestry activities in the marginal strip of the river, in addition to human settlement during the fishing season (Barile et al, 2020). The loss of this natural physical barrier disrupts the dynamics between the river and riverine vegetation favoring the direct entry of an excesses of agrochemicals and fertilizers into the river system, which affects the chemical characteristics and composition of the river biota.…”
Section: Resultsmentioning
confidence: 99%